The effect of barrier hops and bench jumping exercises on increasing Inkado athletes’ speed in mawashi geri - Leni Marlina; Syamsuar Syamsuar; Damrah Damrah; Ilham Ilham; Septri Septri; Alexandre Sibomana (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2023)
This study aim to determineeffect of barrier hops and bench jumping exercises on increasing Inkado athletes’ speed in mawashi geri. This study employed an experimental method with a two groups pretest-posttest design. The research population was athletes form Inkado Tanjungpinang City. The sampling technique used purposive sampling, with the criteria that (1) attendance was at least 75% (actively participating in training). (2) sampel were athletes who participated in training at Dojo Inkado Tanjungpinang City with an age range of 9-19 years, (3) gender male and female. (4) the length of the training period is at least 6 months. Based on these criteria, there were 24 people. Tthe barrier hops hypothesis test with a significant value of 0.000, jumping up and down the bench is 0.000, and the corparison of the two experiments is 0.119. The results showed that based on the T test found a significant value of 0.119 greater than 0.05. These results explain that there is no significant difference between the Posttest Barrier Hops Exercise and Bench Jump Exercises for Mawashi Geri in Karate. The Posttest average of the Barrier Hops group was 72.83 and the group Jumping Up and Down the Benc had an average of 74.00. seen from the difference in the posttest value of barrier hop and jumoing up and down the banch is 1.167. Thus the duffereence in the posttest shows that jumping up and down the bench is better than barrier hops exercise to improve mawashi geri in karate.